Digital game-based learning and creativity in elementary fraction learning: a factorial study using match-up wordwall - Dewi Astuti Suwarno; Mardiyana Mardiyana; Supianto Supianto (Universitas Ahmad Dahlan, 2026)
Fractions are a foundational topic in elementary school mathematics, and many fourth-grade students struggle with them because the topic demands abstract reasoning. Yet few studies have tested how such game media interact with students' creativity levels in fraction learning. This study examined how learning media and student creativity levels affect fraction learning outcomes. A quasi-experimental design with a 2 × 3 factorial structure was used. The first factor was the learning media, namely the Match Up game media and PowerPoint. The second factor was student creativity, understood here as creative thinking skill and classified according to the hierarchical framework of Subanji and Nusantara. The participants were 62 fourth-grade students from the Diponegoro Cluster public elementary schools in Wonogiri Regency, with 32 students in the experimental group and 30 in the control group. Fraction learning outcomes were measured with a 16-item multiple-choice test. Creativity was measured with a three-item essay test scored against a rubric, and the students were then grouped into high, medium, and low creativity levels. The data were analyzed with a two-way ANOVA with unequal cell sizes, followed by the Scheffé post hoc test. Three main results emerged. First, the Match Up group obtained a better mean score (M = 80.27) than the PowerPoint group (M = 71.46), with F = 7.4677 and p = 0.008. Second, students with high and medium creativity scored significantly better than their low-creativity peers, with F = 6.6645. Third, media and creativity interacted significantly, with F = 7.5431, meaning that the effect of the media depended on the students' creativity level; the advantage of Match Up was largest among highly creative students. These findings add to the evidence on digital game-based learning in elementary school mathematics and suggest that teachers can use Match Up for differentiated instruction that matches media features to students' creativity profiles. The main contribution of this study is evidence that the benefit of digital game-based media is conditional on students' creativity rather than uniform, which extends earlier Wordwall studies that reported only average effects.